The impact of the IFRS 15 implementation on the revenue-based earnings management in Poland - Morawska Izabela (Journal of Economics and Management, 2021)
Aim/purpose – This paper aims at investigating whether the International Financial Reporting Standard (IFRS) 15 Revenue from Contracts with Customers implementation in Poland has affected earnings management that uses discretion in revenue recognition to avoid losses and earnings decreases.